Enhancing Students’ Reader Response through Intellectual Diary in Hemingways’ The Old Man and The Sea - Ahmad Rizal Abdullah (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study investigates the effectiveness of the Intellectual Diary (ID) strategy in enhancing EFL students' Reader Response Competence during the reading of Ernest Hemingway’s novella, The Old Man and the Sea. Grounded in Rosenblatt's (1978) transactional theory, the study addresses the challenge of passive reading by implementing the ID as a structured reflective tool. This qualitative descriptive research involved 28 undergraduate students from an Indonesian state university. Data were collected from 112 Intellectual Diary entries, supplemented by interviews and field notes, and analyzed using thematic analysis. The analysis focused on four dimensions of response: interpretative depth, emotional engagement, critical inquiry, and personal reflection. Findings revealed a substantial improvement across all four dimensions, with high overall mean scores (2.75 to 4.00). The ID successfully fostered deeper symbolic understanding (interpretative depth) and significantly enhanced students' personal connection and empathy for Santiago's struggle (emotional engagement and personal reflection). Furthermore, reflective writing encouraged a more critical and questioning stance toward the text. In conclusion, the Intellectual Diary is an effective and theoretically sound pedagogical strategy for transforming reading into an active, transformative process. Its use is strongly recommended for EFL literature classrooms aiming to cultivate reflective, analytical, and emotionally engaged readers.